Optimalisasi Media Sosial sebagai Sarana Publikasi Pengawasan Pemilu 2024: Kasus Bawaslu Kota Tanjungpinang - Ella Afnira (Jurnal Mahasiswa Komunikasi Cantrik, 2023)
The Election Supervisory Body (Bawaslu) is responsible for overseeing elections and preventing violations. To carry out its duties properly, Bawaslu requires community participation. Therefore, Bawaslu increases participatory supervision by providing facilities to report violations. Bawaslu needs to optimize the use of social media as a means of publication so as to facilitate public participation and ensure integrity and accurate election results. This research was conducted to determine the optimization of social media in the monitoring process. Research using the case study method. Data was collected through in-depth interviews, observation, and documentation. The results of the study show that the Tanjungpinang City Bawaslu has attempted to optimize the management of social media as a means of publication. This effort is illustrated in the public relations strategy used. However, there are still some obstacles to be resolved. This study recommends the need for the Tanjungpinang City Bawaslu to evaluate the strategies implemented.